2017
DOI: 10.1002/app.45115
|View full text |Cite
|
Sign up to set email alerts
|

Compressive shape memory behavior of spring‐shaped polylactic acid alloy type

Abstract: This article presents an experimental study on the shape memory behavior of blends of thermoplastic polyurethane (TPU) and biodegradable polylactic acid (PLA) at the PLA/TPU weight ratios of 70/30 (PT7030) and 50/50 (PT5050). The manufactured springs were studied comprehensively based on their morphological and thermal properties. Scanning electron microscopy micrographs were captured, which verified that TPU was compatible with PLA. The wide‐angle X‐ray diffraction suggested that the crystallinity of PLA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In the COS 1 HNMR spectrum, the peak at 1.98 ppm was attributed to -CH 3 in the N-alkylated glucosamine residue, and singlet H peak for N-acetyl glucosamine was observed at 2.98 ppm; there was a multistate peak at 3.45–4.12 ppm, which was due to the chemical shift of -CH- on the sugar ring and proton hydrogen at 6C. The peak at 4.58 ppm was attributed to H of glucosamine [ 30 ]. In addition to the chemical shift of H in COS, the absorption peak of the benzene ring and the chemical shift of -HC=N appeared at 7.73–8.33 ppm and 10.12 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the COS 1 HNMR spectrum, the peak at 1.98 ppm was attributed to -CH 3 in the N-alkylated glucosamine residue, and singlet H peak for N-acetyl glucosamine was observed at 2.98 ppm; there was a multistate peak at 3.45–4.12 ppm, which was due to the chemical shift of -CH- on the sugar ring and proton hydrogen at 6C. The peak at 4.58 ppm was attributed to H of glucosamine [ 30 ]. In addition to the chemical shift of H in COS, the absorption peak of the benzene ring and the chemical shift of -HC=N appeared at 7.73–8.33 ppm and 10.12 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable research has been devoted to the development of novel BSMP formulations that have the potential for use in medicine. For recent examples we direct the reader to the following references . In the Becker lab, we have developed amino acid‐based poly(ester urea)s (PEUs) and explored their shape memory behavior .…”
Section: Future and Outlookmentioning
confidence: 99%
“…They found that compared to the non-foam state, the formation of foam structure in the alloys led to a significant reduction in the recovery force. Siahsarani et al 34 manufactured a spring shape memory polymer from the alloy composition of PLA and TPU. They investigated the compression shape memory behavior of the samples, and according to the results, the composition containing a higher percentage of polylactic acid (70% weight percentage) has the highest shape and force recovery.…”
Section: Introductionmentioning
confidence: 99%